2015
DOI: 10.1089/cbr.2014.1723
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Tumor Protein D52-Like 2 Contributes to Proliferation of Breast Cancer Cells

Abstract: Cancer Biotherapy and Radiopharmaceuticals (CBR) is officially retracting the published article by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 23 publications
(24 reference statements)
0
25
0
Order By: Relevance
“…40,41 Yang et al demonstrated that knockdown of TPD52L2 (a member of the TPD52) suppressed the proliferation and colony formation in BC cells. 42 Zhang et al found that TPD52 expression was markedly increased in BC tissues and cells, and deficiency of miR-449 promoted proliferation and metastasis of BC cells through regulating TPD52. 27 In our research, results uncovered that TPD52 expression was enhanced in TNBC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Yang et al demonstrated that knockdown of TPD52L2 (a member of the TPD52) suppressed the proliferation and colony formation in BC cells. 42 Zhang et al found that TPD52 expression was markedly increased in BC tissues and cells, and deficiency of miR-449 promoted proliferation and metastasis of BC cells through regulating TPD52. 27 In our research, results uncovered that TPD52 expression was enhanced in TNBC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…PubMed ''similar'' searches were performed to identify papers that PubMed recommended as similar to one index paper (Yang et al 2015). The PubMed ''similar'' search 4 is based on a similarity function that differently weights words from the abstract, title and MeSH words (Medical Subject Headings).…”
Section: Pubmed Corpusmentioning
confidence: 99%
“…The PubMed ''similar'' search 4 is based on a similarity function that differently weights words from the abstract, title and MeSH words (Medical Subject Headings). When searching for papers ''similar'' to Yang et al (2015), the retrieved set may contain papers that are similar or quite dissimilar, as mea-sured using intertextual distance (see below). Nevertheless, a PubMed ''similar'' search can be viewed as a first step to identify a set of papers with a greater chance of being similar (within the meaning of intertextual distance) to members of the index corpus.…”
Section: Pubmed Corpusmentioning
confidence: 99%
See 2 more Smart Citations